Estudos de prevenção da corrosão de refratários utilizados em carro-torpedo - Justus, Sergio Murilo (Universidade Federal de São Carlos, 2004)
The high competitiveness generated by the world metallurgical scenery has been taking the Integrated Steelworks to look for an incessant way the increase of the efficiency of the refine pre-treatment processes, especially Pig Iron Hot Metal Desulfurization at Torped Car. As collateral effect, the refractory lining used in these equipment has been submitted to operational conditions more and more severe leading to an increasing the wear rate. In this sense, the Post Mortem Study of a based Al2O3/SiC/C/MgAl2O4 refractory lining (ASCM) used at CSN Torped Cars was carried out. It was concluded that a slag containing a big amount of calcium aluminum-silicate, interacts with the refractory microstructure promoting the corrosion. It was also identified a concurrent mechanism by alkaline incorporation, besides corundum to betaalumina transformation and SiC oxidation by Na2O resulting in better conditions to the graphite of protection, and consequently, improving the refractory lining campaign. In order to prevent the corrosion of the Torped Car Refractory Lining, a new technology was developed by using a Impregnation Technique of the Cerium Solution SIT/Ce, which the Cerium Solution is able to fill up partially the opened porous of the ASCM microstructure, improving the corrosion resistance and thermal-mechanical properties. The protection mechanism was identified carrying out dynamic slag test and fracture energy test, followed by microstructure characterization by using of the Scanning Electronic Microscopy (SEM), X-Ray Diffraction and Mercury Porosimeter. Another New Protection Technology of Torped Car Refractory Lining was also developed based on Protecting Layer Formation - FPL. This technique consists of changing the Slag Composition, resulting in an improved wear resistance. Preliminary simulations were carried out in order to optimize the dopant concentration at the slag, followed by tests in rotative oven simulating the wettability refractory material by doped slag. As consequence the Technology of FPL was implemented at Industrial Scale resulting in an additional Protection Mechanism of CSN Torped Car Refractory Lining. By taking account the ASCM refractory lining microstructure, it was observed that main corrosion spots are located in the material fine fraction (matrix). Besides, the matrix which includes the primary bonding system, additional pores are generated to the existing ones as consequence of the resin oxidation during Torped Car heating up. Therefore, it was evaluated the effect of the Doping Bonding System in relation to the thermal and mechanical properties and corrosion resistance. It was achieved an improvement of both indicating the feasibility of The Doping Technique of the Bonding System – DBS/CeO2.
Corrosion prevention study of al2o3/sic/c/mgal2o4 refractories used in torpedo car
Keywords: Corrosão; Materiais refratários; Carro torpedo; Ferro gusa; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO